Remating opportunities and low costs underlie maternal desertion. (9th December 2022) - McDonald, Grant C; Cuthill, Innes C; Székely, Tamás; Kosztolányi, András
Abstract: Parental care can enhance offspring survival but may impose significant costs to parents. The costs and benefits of care are key to understanding patterns of parental care, where parents can benefit by having their partner increase investment in care, while reducing their own effort. However, investigating the costs and benefits of parental care in wild populations is challenging. Here we use highly detailed behavioral observations in families of a small shorebird, where one parent frequently deserts its offspring, to explore the potential costs and benefits of desertion in a wild population. We first show that females desert their broods more frequently than males. Second, we investigate the benefits of this frequent female desertion in terms of additional mating opportunities, and the costs of desertion to females in terms of the growth and survival of deserted offspring. Our results indicate that female desertion is favored by a combination of remating benefits and a lack of costs to brood growth and survival, as abandoned male parents continue to provide care after desertion. Our results shed light on the costs and benefits underlying natural desertion strategies and suggest that female desertion is a fine-tuned behavior that responds to seasonally changing benefits of desertion.